Student Self-Assessment in Islamic Religious Education: A Scopus-Based Bibliometric Review of Trends, Themes, and Research Gaps - Moh Sahlan; Kusaeri; Suprapto; M. Sukron Djazilan (Universitas Nahdatul Ulama Surabaya, 2025)
The central problem addressed in this study is the fragmented nature of existing research on student self-assessment within the context of Islamic Religious Education (IRE). This fragmentation hampers the identification of developmental trends, dominant themes, and comprehensive research trajectories in the field. Although self-assessment, as a reflective evaluative strategy, holds significant potential for enhancing metacognitive awareness, learner autonomy, and the cultivation of students’ religious character, its implementation has not been supported by systematic scientific mapping. Accordingly, this study aims to analyze publication trends, collaboration patterns, and the thematic evolution of research on student self-assessment in IRE using a bibliometric approach. The study employed a bibliometric design with data sourced from the Scopus database covering the period 1990–2025. A total of 169 relevant documents were analysed using Bibliometric (RStudio) and VOSviewer to map citation patterns, author collaborations, and keyword and thematic clusters. The analytical techniques included co-citation analysis, co-authorship analysis, bibliographic coupling, and keyword co-occurrence mapping. The results indicate that research on self-assessment has experienced moderate growth, with an annual development rate of 5.25%. The dominant themes identified include formative assessment, self-regulated learning, and professional development, with recent trends increasingly reflecting the integration of digital technology and artificial intelligence in reflective assessment practices. Nevertheless, international collaboration remains relatively limited, and studies specifically situated within the IRE context are still scarce. Based on these findings, future research is encouraged to develop self-assessment models grounded in Islamic values and supported by digital technologies, as well as to strengthen cross-country collaborations to enrich reflective evaluation practices in Islamic education.